Faktor-Faktor Yang Mempengaruhi Keikutsertaan Petani Dalam Program Asuransi Usaha Tani Padi (Autp) Di Kecamatan Tungkal Ulu Kabupaten Tanjung Jabung Barat - Fikri Siregar, Muhammad; Alamsyah, Zulkifli; Ningsih, Rozaina (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2022)
This study aims to 1) find out the description of the characteristics of farmers who follow AUTP and farmers who do not follow AUTP, 2) study the implementation of AUTP and 3) analyze the factors that influence farmer participation in the AUTP program. The research was conducted in Tungkal Ulu District with the number of respondents as many as 31 farmers who participated in the AUTP and 31 farmers who did not participate in the AUTP. Data were analyzed using logistic regression analysis. The results showed that 1) farmers who participated in AUTP had lower characteristics of age, number of family members, and farming experience compared to farmers who did not participate in AUTP, while the level of education, land area, intensity of crop failure and information about AUTP groups of farmers who participated in AUTP higher than farmers who did not participate in AUTP in Tungkal Ulu District, Tanjung Jabung Barat Regency. 2) The implementation of AUTP in Tungkal District is generally in accordance with the AUTP Guidelines but the lack of socialization is the cause of the low participation of farmers in the AUTP program and the low knowledge of farmers about insurance claims. 3) The results of the analysis showed that the factors of age, land area, crop failure intensity and AUTP information had a significant effect on farmers' participation in the AUTP program, while education, number of family members and farming experience had no significant effect on farmers' participation in the AUTP program in Tungkal Ulu District.